Leprosy Reactions and Neuropathic Pain in Pure Neural Leprosy in a Reference Center in Rio de Janeiro – Brazil - Pitta, Izabela Jardim Rodrigues; Hacker, Mariana Andrea; Vital, Robson Teixeira; Andrade, Ligia Rocha; Spitz, Clarissa Neves; Sales, Anna Maria; Antunes, Sergio Luiz Gomes; Sarno, Euzenir Nunes; Jardim, Marcia Rodrigues (Frontiers in Medicine, 2022)
Introduction Leprosy reactions are complications that can occur before, during, or after multidrug therapy (MDT) and are considered a major cause of nerve damage. Neuritis is an inflammatory process that causes nerve function impairment associated with pain and tenderness along the nerve. Neuritis can be found in both type 1 and type 2 reactions and may also be the sole manifestation of a leprosy reaction. The objective of this study is to describe the incidence of leprosy reactions and its association with neuropathic pain in pure neural leprosy (PNL) patients. Methods We selected 52 patients diagnosed with PNL and 67 patients with other clinical forms of leprosy. During the MDT the patients visited the clinic monthly to take their supervised dose. The patients were instructed to return immediately if any new neurological deficit or skin lesions occurred during or after the MDT. Results Of the PNL patients, 23.1% had a leprosy reaction during or after the MDT, while this was 59.7% for patients with the other clinical forms of leprosy. There was an association between having PNL and not having any reaction during and after the MDT, as well as having PNL and having neuritis after the MDT.There was also an association between having previous neuritis and having neuropathic pain in the other clinical forms of leprosy group, although this association was not present in the PNL group. Discussion Our data suggest that PNL is a different form of the disease, which is immunologically more stable. In addition, PNL patients have more neuritis than the classical leprosy skin reactions. In PNL there was no association between acute neuritis and neuropathic pain, suggesting that these patients may have had silent neuritis. Understanding and identifying neuritis is essential to reduce disability and the impact on public health.